The Influence of Campus Promotion, Service Quality and Accreditation on the Interest of New Students at PSDKU Aru - Johan Pieter Elia Rumangun; Titus Welerubun (JETISH: Journal of Education Technology Information Social Sciences and Health, 2002)
This study aims to empirically examine the influence of Campus Promotion, Service Quality and Accreditation on New Student Interest in Psdku Aru. The population in this study was All New Students in Psdku Aru, Aru Islands Regency. The sample in this study was a New Student of the Law and Accounting Study Program of PSDKU Unpatti in the Aru Islands Regency. The sampling technique used is Purposive Sampling, which is a sample with criteria, namely New Students of Law and Accounting Study Program. The research method used is a quantitative research method. The data were obtained through the dissemination of questionnaires and measured using a simple regression analysis processed through SPSS 23 software.